Descrição de verbos de base adjetiva derivados com os sufixos -ecer e -izar, para o processamento automático de linguagem natural - Picoli, Larissa (2015)
This research presents a syntactic-semantic description of verbs derived from adjectives with suffix –ecer, for example, enriquecer “enrich”, amadurecer “ripen” and fortalecer “strengthen”, and with suffix –izar, for example, banalizar “banalize” and suavizar “soften” in pairs of simple sentences like: (1) A herança enriqueceu Pedro “The heritage enriched Pedro”, (1a) A herança tornou Pedro rico “The heritage made Pedro rich” and (2) O aumento da renda banalizou as viagens “Rising incomes trivialized travel”, (2a) O aumento da renda tornou as viagens banais “Rising incomes made the banal travel”, in order to observe the semantic correspondence between base sentences (1) and (2) and transformed sentences (1a) and (2a). The description of the verbs is based on a list of deadjectival verbs in –ecer and –izar collected through searches in dictionaries, in the web and by introspection. From these verbs, simple sentences are built to observe their syntactic-semantic properties. The analysis of syntactic-semantic properties of the verbs is carried out within the theoretical-methodological model of Lexicon-Grammar (1975), defined by linguist Maurice Gross. These properties are encoded through syntactic formulas. The description of the structures’ properties allows for the elaboration of a language resource in the format of a Lexicon-Grammar table. The table is composed of a list of 88 deadjectival verbs with suffix –ecer and 84 verbs with–izar. The encoded description of the properties of verbs can be included in a data base for Automatic Processing of Natural Language (PLN).